PERENCANAAN PEMBANGUNAN DAERAH DALAM ERA OTONOMI DAERAH (Universitas Suryakancana, 2020)
Law Number 23 Year 2014 concerning Regional Government expressly wants that in this era of centralized regional government system towards decentralization, regional government and the community as well as all stakeholder components. The government must be able to direct various policies in the form of a framework for the implementation of regional autonomy policies at a point of accelerating the welfare of society through improving public services and optimizing the participation of the community in the process of regional autonomy in development.The author in this study wants to examine and analyze further the urgency of regional development planning in the era of regional autonomy and the obstacles and strategies for implementing regional development plans in the era of regional autonomy.The research method used is normative legal research, namely legal research carried out by examining library materials or secondary legal materials while the problem approach is carried out using a legal approach and conceptual approach.Development planning in a country or society that can be cultivated starting from the economy, natural resources. Human Resources and Infrastructure because the output of regional development planning is that local governments must encourage the achievement of a development plan based on regional planning. The preparation of the plan will always face obstacles in the form of unwillingness and the inability of the compiler to capture the philosophy and autonomization of the region. Keywords: Regional Government, Policy, Development Planning.